Summer democracy school - Malik, Maszlee (2016)
The primary objective of conference is to understand the nature of democracy and how it is compatible with Islam. The Seminar was specially organised to explained to the participants which mainly come from government agencies, uniform bodies and university students, on the needs of democracy in modern world. The variety of presenters from local and international agencies and higher learning institutions has shed the bigger picture of what democracy is, and how it is in comply with Islamic teaching. The seminar was launched and patroned by the Governor of Acheh himself due to the importance of the issue discussed.